A report on the extraction practice of quack dentists in six barrios in the Philippines - Perfecto Jr., Edmundo I.; Sustento, Rafael; Bunag, Celso A. (Adviser).
This report contains some observations on the extractions practice of some quack dentist in six different barrios in the Philippines. Data gathered is hoped to provide researchers with base-line information that could be of use in the conduct of more in depth studies on the subject. It was observed that diagnosis and asepsi, important components of exodontia, were not observed by all the quack dentists. Neither did they observe specific positioning for both the operator and the "patient nor specific movements for the operator. Handkerchiefs, forceps, pieces of cloth, ballpens, white paper and cotton swabs were regularly utilized as instruments. Though they all claimed having prayers at their command to invoke a supernatural power to aid them during extraction, all of the quack dentists observed admitted their infraquent usage of their prayers. To control the bleeding, they made "patients" gurgle with water, drink cold calamansi juice and apply pressure on the treated area. Donations not service fees were accepted by the quack dentists. To further understand their extraction practice and the extent of their influence on people in the rural areas, a more thorough study is recommended.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.